Synthesis and antiviral evaluation of novel heteroarylpyrimidines analogs as HBV capsid effectors. Issue 4 (15th February 2017) - Boucle, Sebastien; Lu, Xiao; Bassit, Leda; Ozturk, Tugba; Russell, Olivia Ollinger; Amblard, Franck; Coats, Steven J.; Schinazi, Raymond F.
Graphical abstract: Abstract: New modifications to the scaffold of previously reported HBV capsid assembly effectors such as BAY 41-4109, HAP-12 and GLS4 were explored. The anti-HBV activity in the HepAD38 system, and cytotoxicity profiles of each of the new compounds has been assessed. Among them, five new iodo- and bromo-heteroarylpyrimidines analogs displayed anti-HBV activity in the low micromolar range.